FIELD ASSESSMENT AND MOLECULAR MARKERS-BASED CHARACTERIZATION OF YELLOW RUST RESISTANCE IN WHEAT HYBRID PROGENIES - S. N. Khan; G. Hassan; M. R. Khan; Z. H. Facho; D. Singh; K. S. Sandhu; M. Sanaullah; M. Imtiaz; S. Ali (Journal of Animal and Plant Sciences, 2022)
Yellow rust is one of the major production constraints of wheat in Pakistan. To accelerate development of rust resistant cultivars, field testing may be accompanied with molecular genotyping. In the present studies, 56 F1 wheat hybrids were developed through 8×8 full diallel crosses during 2014-15. All the 56 F1 wheat hybrids along with parental genotypes were evaluated during 2015-16 under rainfed and irrigated conditions to identify yellow rust resistant genotypes. Pooled analysis of variance revealed highly significant (P < 0.01) differences among the genotypes for final rust severity, relative area under disease progress curve and average co-efficient of infection. Under both environments, 41 genotypes showed high, 7 moderate while remaining genotypes showed low level of partial resistance. Under rainfed condition, genotypes PS-05×AH, PS-05 and PS-13×PS-05 while under irrigated condition, Lal-13×JB, PS-05×Lal-13, PS-05×Tat-96 and JB×PS-05 were partially resistant in the field. The presence of yellow rust resistance genes, Yr5, Yr17 and Yr18, were confirmed in 76%, 78% and 37% genotypes respectively, using molecular markers, which were present either individually or in combinations of two or three genes. Among the parents, PS-13, JB and PS-05 performed well under both conditions. Under irrigated condition, cross combinations, Lal-13×JB, KW×PS-05 and JB×AH while under rainfed condition, genotypes PS-05×PJ-11, Tat-96×AH and JB×AH, showed best performance in terms of yield and rust resistance. Cluster analysis grouped majority of partial resistance genotypes into sub cluster G1. Field testing and molecular markers analysis, revealed the presence of variability in resistance among the studied genotypes.
Keywords: Stripe rust; Wheat Hybrids; Genetic improvement; Peshawar